Biomass production and partitioning and structural parameters of trunk and leaf in Butterfly Pea fertilized with phosphorus Produção e partição da biomassa e parâmetros estruturais do caule e da folha da cunhã adubada com fósforo - Jadson Miranda Oliveira (Revista Brasileira de Saúde e Produção Animal, 2010)
The experiment was conducted in a greenhouse of DTCS-UNEB, to evaluate the phosphorus fertilization (0; 25; 50; 75 and 100kg/ha of P2O5) in production and partition of biomass of part aerial and root, beyond the structural parameters of the trunk and leaf of Butterfly Pea (Clitoria ternatea L.). The experimental design was completely randomized, with five doses phosphorus and four repetitions. After 20 days of sowing, the plantule were transplanted, and five days later fertilized with the treatments, at the beginning of the experiment until 45 days, when the plant were harvested and evaluated. The phosphorus increased the production of biomass of part aerial in the maximum dose (Ymáx) of 100kg/ha in the trunk at 100kg/ha, in leaf at 98.65kg/ha and in root at 52.10kg/ha of P2O5 with a production of 17.59, 3.86, 11.28 and 1.86g/pot, respectively. For the structural parameters of the trunk, only the trunk diameter and flower button number per plant was increased with phosphorus fertilization, resulting in increased production in 68.21 and 100kg/ha of P2O5, equivalent to the 4.53mm and 7.51 flower button per plant, respectively, and to the structural characteristics of the leaves, there was an increase only in the number of expanded leaf in the secondary branches up to 68.21kg/ha P2O5 with 3.54 expanded leaves/secondary branch. Within the context of present research, to the largest accumulation of biomass of forage from the part aerial of Butterfly Pea, used in animal feed, the best response was in a 100kg/ha of P2O5. O experimento foi conduzido na casa de vegetação do DTCS-UNEB, com objetivo de avaliar a adubação fosfatada (0; 25; 50; 75 e 100kg/ha de P2O5) na produção e partição da biomassa da parte aérea e raiz e nos parâmetros estruturais do caule e da folha de cunhã (Clitoria ternatea L.). O delineamento experimental foi inteiramente casualizado, com cinco doses fósforo e quatro repetições. Após 20 dias da semeadura, as plântulas foram transplantadas e, cinco dias depois, adubadas com os tratamentos, do início do experimento até os 45 dias, quando foram colhidas e avaliadas. O fósforo aumentou a produção da biomassa da parte aérea e do caule até a dose (Ymáx) de 100kg/ha; na folha, até 98,65kg/ha, e na raiz, 52,10kg/ha de P2O5, com uma produção de 17,59; 3,86; 11,28 e 1,86g/vaso, respectivamente. Para os parâmetros estruturais do caule, apenas o diâmetro do caule e o número de botões florais/planta foram incrementados com a adubação, de forma que se obteve maior produção em 68,21 e 100kg/ha de P2O5, equivalentes a 4,53mm e 7,51 botões florais/planta, respectivamente. Para as características estruturais das folhas, houve aumento somente no número de folhas expandidas por ramo secundário, que foi até 68,21kg/ha de P2O5, com 3,54 folhas expandidas/ramo secundário. Dessa forma, o maior acúmulo de biomassa de forragem da parte aérea da cunhã é alcançado na dose de 100kg/ha de P2O5.